The plant amino acid mimosine may inhibit initiation at origins of replication in Chinese hamster cells. - Mosca, P J (1992)
An understanding of replication initiation in mammalian cells has been hampered by the lack of mutations and/or inhibitors that arrest cells just prior to entry into the S period. The plant amino acid mimosine has recently been suggested to inhibit cells at a regulatory step in late G1. We have examined the effects of mimosine on cell cycle traverse in the mimosine [corrected]-resistant CHO cell line CHOC 400. When administered to cultures for 14 h after reversal of a G0 block, the drug appears to arrest the population at the G1/S boundary, and upon its removal cells enter the S phase in a synchronous wave. However, when methotrexate is administered to an actively dividing asynchronous culture, cells are arrested not only at the G1/S interface but also in early and middle S phase. Most interestingly, two-dimensional gel analysis of replication intermediates in the initiation locus of the amplified dihydrofolate reductase domain suggests that mimosine may actually inhibit initiation. Thus, this drug represents a new class of inhibitors that may open a window on regulatory events occurring at individual origins of replication.